Effects Of Plant Support System And Intercropping With Long Bean (Vigna Sinensis) On Growth, Yield And Fruit Quality Of Red Dragon Fruit (Hylocereus Polyrhizus). - Mohammad Yusoff, Martini (2006)
Climbing epiphytic cacti, particularly members of the genera Hylocereus known as pitaya or dragon fruit, have recently drawn much attention of growers worldwide because of their economic value as food products and also owing to their high nutritive and medicinal values. These cacti are branched climbers needing strong structures to ensure their vigorous growth and heavy fruit yield for maximum yield production. Various designs of structure have been used to provide such support. In addition, it normally takes 12 to 18 months for dragon fruit to bear fruits after planting. Thus, it would be useful if intercropping could be practiced during this juvenile period of dragon fruit. Therefore a study was conducted to determine the effects of using three plant support systems, the pole, T bar trellis and V shape on growth, yield and fruit quality of dragon fruit and to evaluate the use of long bean as an intercrop with dragon fruit.